2009
DOI: 10.1556/achrom.21.2009.3.9
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS study of the performance of different techniques for isolating the volatile fraction from sage (SalviaL.) species, and comparison of seasonal differences in the composition of this fraction

Abstract: Application of chemotaxonomy to the plant kingdom can be regarded as a future challenge to the traditional binomial classification system. Construction of a classification system based on the chemical composition of plants has only recently become possible with the development of sophisticated chromatographic and hyphenated techniques. Successful chemotaxonomy can, however, be achieved only if sufficient experimental evidence is collected confirming the reproducibility of the chemical composition of plant spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
1
5
1
Order By: Relevance
“…In fact, previous works [11,15,[17][18][19] on the essential oils of S. staminea have quite different variation with the present work for the volatile organic compounds.…”
Section: Introductioncontrasting
confidence: 67%
See 2 more Smart Citations
“…In fact, previous works [11,15,[17][18][19] on the essential oils of S. staminea have quite different variation with the present work for the volatile organic compounds.…”
Section: Introductioncontrasting
confidence: 67%
“…Myrcene, linalyl acetate, valencene, spathulenol, β-springene, sclareol, and cyclohexanone in HD, myrcene, linalyl acetate, and E-caryophyllene in SPME and linalyl acetate in HS were found to be major compounds. In the previous studies, the volatile composition and antimicrobial activity of the essential oils of S. stamenia collected from the botanical garden have been studied [11,15] and the major components of the essential oil for S.staminea were mentioned to be α-pinene, camphene, β-pinene, limonene, eucalyptol and β-chamigrene [11,15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common technique used for the analysis of volatile components is gas chromatography coupled with a flame ionization detector (GC-FID) or with a mass spectrometry detector (GC-MS), because these methods provide qualitative and quantitative data, even for complex mixtures, with high sensitivity and resolution. Some studies have reported the relative quantitation of SlEO from other Spanish regions [ 1 , 7 , 13 , 14 , 15 , 16 ] and from other countries (Poland [ 17 ], Germany [ 12 ] and Brazil [ 18 , 19 ]). None of them have studied SlEOs from Murcia nor made a chiral characterization of the EOs from this species.…”
Section: Introductionmentioning
confidence: 99%
“…Its components were totally different with Iranian one and its major components were β-chamigrene (10.12-12.08 %), cadin-3,9-diene (6.30-6.39 %) and α-pinene (2.64-6.36 %) 15 . In some reports on chemical composition of the essential oils belonging to Salvia genus existing in Iran, β-caryophyllene and α-pinene were reported as the main compounds [16][17][18][19][20][21][22] .…”
Section: Resultsmentioning
confidence: 82%